Auto-destruction or auto-reproduction? - Julianna Blair Watson (Francosphères)
This article addresses the literary aesthetics of extreme violence in Yasmina Khadra’s A quoi rêvent les loups. In Khadra’s descriptions of violence a flood of words erupt which graphically detail the horrors of the war in Algeria in the 1990s. Literary criticism on African literary violence has largely focused on the notions of the ‘unspeakability’ or ‘unrepresentability’ of violence in Africa. Khadra’s linguistic excess, though, by its very nature writes against these notions through a surplus of representability in order to counter the idea that violence has become endemic and banal in Africa. Khadra’s writing further shows that the war’s carnage is and must be representable in order to confront an historical legacy of violence which is flowing back and forth in time to underscore the (anti-)colonial roots of violence in postcolonial Algeria.